2012
DOI: 10.1016/j.jebo.2012.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Price increasing competition? Experimental evidence

Abstract: Economic intuition suggests that increased competition generates lower prices. However, recent theoretical work shows that a monopolist may charge a lower price than a firm facing a competitor selling a differentiated product. The direction of the price change when competition is introduced is dependent upon the joint distribution of buyer values for the two products. We explore this relationship using controlled laboratory experiments. Our results indicate that the distribution of buyer values does affect pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…However, studies have shown that a monopolist may charge lower prices than a company facing competitors selling differentiated products [15]. In any case, an effective pricing strategy is very important to help enterprises formulate quotations consistent with the competition, maximize revenue and make rich profits [16]. With the increase of e-commerce sales and the realization of frictionless comparative shopping digital commerce, the market competition has become more intense and real-time.…”
Section: Figure 4 Numbers Of American Adults Use the Internetmentioning
confidence: 99%
“…However, studies have shown that a monopolist may charge lower prices than a company facing competitors selling differentiated products [15]. In any case, an effective pricing strategy is very important to help enterprises formulate quotations consistent with the competition, maximize revenue and make rich profits [16]. With the increase of e-commerce sales and the realization of frictionless comparative shopping digital commerce, the market competition has become more intense and real-time.…”
Section: Figure 4 Numbers Of American Adults Use the Internetmentioning
confidence: 99%